Integration of nutrition into extension and advisory services: A synthesis of experiences, lessons, and recommendations - Fanzo, Jessica; Marshall, Quinn; Dobermann, Darja; Wong, Joyce; Merchan, Rafael I.; Jaber, Mona I.; Souza, Alejandro; Verjee, Neelam; Davis, Kristin E. (SAGE Publications, 2015)
The need for nutrition-sensitive agriculture is well recognized and of growing interest to global development players. Extension and advisory services (EAS), with their established infrastructure, provide a unique opportunity for nutrition interventions to be implemented at scale with significant reach.To assess current integration of nutrition in EAS, document training provided to EAS agents, and identify challenges and opportunities for the integration of nutrition.A mixed methodology was used, which included a systematic literature review covering the following databases: PubMed, ISI Web of Science, Agris, Google Scholar, Econlit, and IBSS. In addition, online surveys and semistructured key informant interviews with stakeholders were performed. Data were collected between December 2012 and June 2013.Based on this study, the most common integration of nutrition into EAS is through efforts to increase the availability of nutritious food. The nutrition training of extension agents is often inadequate, particularly in the realm beyond technical agricultural skill. Additionally, a lack of career opportunities discourages EAS agents form engaging with nutrition integration. The major challenges to integrating nutrition into EAS centered on lack of training for agents, unclear organizational mandates, lack of female inclusion, lack of mobility, and systemic challenges between agriculture and nutrition sectors. Key opportunities for integration efforts are engaging communities, creating a demand for nutrition, and use of innovative communications.This study demonstrates a large degree of variability across programs in the integration and implementation of nutrition activities into EAS, providing differing opinions on the feasibility of integration. Although the need for nutrition-sensitive agriculture is known, and there is agreement that EAS would provide a positive framework, there are still challenges impeding a simple integration of nutrition into EAS as a delivery platform.